Glancing-angle deposition of magnetic in-plane exchange springs - Frisk, A; Achinuq, B; Newman, DG; Dabrowski, M; Hicken, RJ; van der Laan, G; Hesjedal, T (American Physical Society, 2023)
Magnetic exchange springs (ESs) are composed of exchange-coupled hard and soft magnetic layers, i.e., layers with high and low anisotropy, respectively. The moments in the soft layer can be wound up by applying an external field, which has to be smaller than the anisotropy field of the hard layer. Alternatively, an ES can be realized by biasing the soft magnetic layer by two adjacent hard magnetic layers with different magnetic anisotropy directions. We have fabricated an ES layer stack by magnetron sputter deposition. As the hard magnetic bottom layer, we used epitaxial FePt L10, and as the top layer Co with both layers having different in-plane easy axes. These hard layers pin the moments of a soft permalloy (Ni81Fe19) layer sandwiched between them, winding up an ES at remanence. The anisotropy of the polycrystalline top Co layer was engineered by glancing-angle deposition to have in-plane easy axis anisotropy perpendicular to the easy direction of the bottom layer. Using soft x-ray spectroscopy and magneto-optical measurements, we found the in-plane ES to extend from the soft layer into the top layer of our FePt/permalloy/Co trilayer structure.